Sishen Pill treats spleen-kidney yang deficiency IBS-D by influencing ATPase activity and intestinal microbiota - Long, Qi; Li, Liwen; Tan, Zhoujin; Deng, Na (Frontiers in Microbiology, 2025)
BackgroundSishen Pill (SSP) has therapeutic effects on spleen-kidney yang deficiency diarrhea-predominant irritable bowel syndrome (IBS-D). Studies have shown that IBS-D with spleen-kidney yang deficiency is characterized by intestinal microbiota dysbiosis and impaired ATPase activity. After SSP treatment, the abundance of beneficial microbiota increased, the balance of the intestinal microbiota was restored, and ATPase activity improved, suggesting that SSP may exert its therapeutic effects by modulating the intestinal microbiota and restoring ATPase activity.MethodsForty SPF-grade female mice were randomly allocated into four groups (n = 10 per group): normal group (CC), spontaneous recovery group (MC), pinaverium bromide treatment group (PBT), and SSP treatment group (SSP). The IBS-D mouse model was successfully established by adenine and Folium sennae combined with restraint-tail clamping stress. Following model validation, the animals received SSP aqueous extract treatment. Subsequent evaluations included: (1) assessment of behavioral parameters according to diagnostic criteria; (2) quantification of Na+-K+-ATPase and Ca2+-Mg2+-ATPase activities via ELISA; (3) measurement of intestinal digestive enzyme activity and intestinal microbial activity;(4) characterization of the intestinal microbiota composition via 16S rRNA gene sequencing analysis.Results(1) Compared with CC group, SSP group presented significantly increased Na+-K+-ATPase and Ca2+-Mg2+-ATPase activities (p < 0.05). (2) Enzyme activity assays revealed that digestive enzyme activities were significantly increased in SSP group, with marked increases in lactase and amylase (p < 0.01) and a moderate increase in sucrase. (3) Intestinal microbial activity was notably increased in SSP group (p < 0.01). (4) Correlation analysis showed Clostridioides had a strong positive correlation with lactase (p < 0.01) and positive links to amylase and microbial activity (p < 0.05). Desulfovibrio demonstrated significant negative correlations with microbial activity (p < 0.01). In the comparison between PBT group and SSP group, Ca2+-Mg2+-ATPase showed a positive correlation with Maribacter and Scatolibacter (p < 0.05). Amylase exhibited a significant negative correlation with Scatolibacter (p < 0.01). Fecal microbial activity was negatively correlated with Scatolibacter (p < 0.01).ConclusionSSP significantly alleviates symptoms of spleen-kidney yang deficiency in IBS-D by regulating intestinal microbiota, increasing Na+-K+-ATPase and Ca2+-Mg2+-ATPase activity, and enhancing lactase, amylase and sucrase activity and intestinal microbial activity.